Zombie Book. On Programmed Future and Writing Without the Ultimate Purpose - Paić, Žarko (Poznańskie Studia Slawistyczne, 2019)
The article deals with the analysis of the relationship between art, literature, and democracy, starting with the interpretation of Deleuzeʼs reading of D.H. Lawrence, Apocalypse. It is shown that in the contemporary world we are faced with a radical turn of knowledge, values and ways of thinking. Instead of the word prophecy, the act becomes a vision of transparency that has its most powerful means in the logic of mass media interaction. Hence the image that precedes the world has the potential for transforming the idea of the Book into a post-apocalyptic era of visualization of objects. With the help of Deleuzeʼs concepts such as multitude, difference and becoming, the article focuses on the criticism of the democratic emptiness of the world from which the secret has disappeared, and there has been only writing for survivors, the Book for Zombies. Is this a metaphysical testament at the time when writing has nothing more to do with the reference framework of modern art, when a change in the society could still set goals and tasks?